Case Report: Accuracy analysis of a new scanning body for intraoral digital impressions in full-arch edentulous patients - Ma, Hongyang; Cao, Jia; Tang, Zhihui; Wu, Yuwei (Frontiers in Oral Health, 2025)
This clinical report aimed to compare the scanning accuracy of SRA, and a novel extended scan body in edentulous patients. Through quantitative analysis, the study provided data support for oral prosthodontics and digital treatments. Edentulous patients with six Straumann bone-level implants were selected. The scan data was compared to the standard model derived from traditional impressions to evaluate scanning accuracy. The SRA scan bodies showed lower accuracy (46 ± 45 μm), while the Segma scan bodies with an extended structure achieved significantly higher accuracy (20 ± 2 μm). The extended structure effectively reduced image stitching errors in challenging intraoral regions, improving accuracy and speed. The Segma scan bodies with an extended structure accurately replicated spatial position information of implants in edentulous patients, providing insights for oral prosthodontics and digital treatments to enhance restoration quality.